Answer:
No. pp you can fit in a van: 6,
No. pp you can fit in a bus: 20
Step-by-step explanation:
Let v = # of pp in vans, and let b = # of pp in buses:
8v + 9b = 228,
4v + 5b = 124
If we solve this system of equations by substitution, we isolate the first eq. for v and then substitute into the bottom eq:
v = 228-9b/8,
Substitute v = 228-9b/8 into bottom eq:
[4 * 228-9b/8 + 5b = 125]
[228+b/2=124]
[228+b = 248]
[b = 20]
Now substitute 20 to find no. of pp in the vans:
v = 228 - 9(20)/8 = 228 - 180/8 = 48/8 = 6
Answer:
7 2/3 or 7.666
Step-by-step explanation:
To find the volume of a rectangular prism, multiply its 3 dimensions: length x width x height. The volume is expressed in cubic units.
since we only have two points we have to do
4/3 x 23/4 = 7 2/3 or 7.666
so the answer is 7 2/3 or 7.666
ANSWER
The value of the expression is
![- 1](https://tex.z-dn.net/?f=%20-%201)
EXPLANATION
Method 1: Rewrite as product of
![{i}^{2}](https://tex.z-dn.net/?f=%7Bi%7D%5E%7B2%7D%20)
The expression given to us is,
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4}](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20)
We use the fact that
![{i}^{2} = - 1](https://tex.z-dn.net/?f=%7Bi%7D%5E%7B2%7D%20%20%3D%20%20-%201)
to simplify the above expression.
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0} \times {i}^{1} \times {i}^{3} \times {i}^{2} \times {i}^{4}](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20%20%3D%20%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20)
This implies,
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0} \times {i}^{2} \times {i}^{2} \times {i}^{2} \times {i}^{2} \times {i}^{2}](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20%20%3D%20%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20)
We substitute to obtain,
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = 1\times - 1 \times - 1 \times - 1\times - 1 \times - 1](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20%20%3D%20%201%5Ctimes%20%20-%201%20%5Ctimes%20%20-%201%20%20%5Ctimes%20%20-%201%5Ctimes%20%20-%201%20%5Ctimes%20%20-%201)
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = 1\times 1 \times 1 \times - 1 = - 1](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20%20%3D%20%201%5Ctimes%20%201%20%5Ctimes%20%20%201%20%20%5Ctimes%20%20-%201%20%3D%20%20-%201)
Method 2: Use indices to solve.
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0 + 1 + 2 + 3 + 4}](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20%20%3D%20%7Bi%7D%5E%7B0%20%2B%201%20%2B%202%20%2B%203%20%2B%204%7D%20)
This implies that,
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{10}](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20%20%3D%20%7Bi%7D%5E%7B10%7D%20)
![{i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = ( {{i}^{2}} )^{5}](https://tex.z-dn.net/?f=%20%7Bi%7D%5E%7B0%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B1%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B2%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B3%7D%20%20%5Ctimes%20%7Bi%7D%5E%7B4%7D%20%20%3D%20%20%28%20%20%7B%7Bi%7D%5E%7B2%7D%7D%20%29%5E%7B5%7D%20%20)
9514 1404 393
Answer:
h(-5) = 129
Step-by-step explanation:
Put -5 where x is and do the arithmetic.
h(-5) = 4(-5)² -5(-5) +4
h(-5) = 4(25) +25 +4 = 129
1yd is 12 ft
So do 12-1=11.
11 is the answer